Functional ovarian lesions in children and adolescents: when to remove them - Spinelli, C.; Di Giacomo, M.; Cei, M.; Mucci, N. (Gynecological endocrinology, 2009)
Study objective. Functional ovarian lesions represent 45% of all pediatric adnexal abnormalities. Their surgical management, even if frequent, is not clear, especially in pediatric age. Materials and methods. We retrospectively reviewed 22 pediatric patients surgically treated for functional ovarian lesions from 2000 to 2006. The following characteristics were analysed: age, size of the lesion, ultrasound (US) aspect and clinical presentation. Results. The average age was 16.1 years of age (range: 6 months-18 years). Of the 22 functional lesions, 12 (55%) were follicular cysts and 10 (45%) corpus luteum ones. The average size was 6.7 cm (range: 5.1-33 cm). US scan showed simple lesions in 10 cases (45%) and complex ones in 12 cases (55%). In 16 girls (72.8%) the presenting symptom was abdominal pain while 2 patients (9%) presented abdominal distention. In the other 4 patients (16.2%) the lesion was found accidentally during US examination. Conclusion. In pediatric subjects, functional ovarian cysts rarely required surgical intervention, though no complications or disorder recurrence were reported. To preserve ovarian function, conservative surgery has to be performed whenever feasible.